Lessons Learned from Linking Emissions Trading Systems : General Principles and Applications - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
In support of the partnership for market readiness work on helping the emergence of credible, consistent, and compatible market-based infrastructure across countries, this report reviews the lessons learned from linking greenhouse gas emissions trading systems. Two emissions trading systems (ETS) are linked if a participant in one system can use a compliance instrument (allowance or credit) issued by the administrator of either system for compliance. This report focuses on links that enable participants of both ETS to use compliance instruments from either system (bilateral links). The linked systems can adopt common compliance instruments. Or each system can retain its own compliance instruments and accept those from either ETS for compliance, possibly subject to restrictions. A bilateral link offers three potential benefits. First, it can make an ETS a viable policy option for a jurisdiction where an independent ETS will be infeasible for technical or cost reasons. Second, a bilateral link can reduce the total cost of achieving the combined emissions caps of the linked ETS. Third, a bilateral link can enhance the operation of the market for the compliance instrument(s). Section one gives background information. Section two presents the types of links an ETS can establish and discusses the potential benefits and risks of linking. The requirements for a bilateral link between two ETS are summarized in section three. How to implement a bilateral link is discussed in section four.